Satellite remote sensing of Antarctic sea-ice roughness using scatterometer data - Alexander Fraser; Toyota, T; Jansen, PW; Kimura, N; Jan Lieser; Guy Williams; Trujillo, E; Leonard, K; Maksym, T; Robert Massom (2014)
While sea-ice concentration is frequently observed from polar orbiting passive microwave satellite instruments, equivalent large-scale information on sea-ice sub-metre-scale roughness is currently unknown. Roughness on this scale is closely related to sea-ice thickness, and has implications for primary productivity near the ice/ocean interface, and flow-on effects for ecosystems. C-band (~5 GHz) off-nadir microwave backscatter strength from sea ice is sensitive to many physical characteristics of the sea ice. During summertime and early autumn, liquid water-related processes dominate backscatter variability (formation of melt water and superimposed ice, snow/ice interface flooding). However, during freezing conditions, backscatter variability reduces in the inner pack, and backscatter becomes more representative of snow/ice interface or air/snow interface roughness (dry snow on the order of 1 m thick is largely transparent at C-band, though experimental results suggest a significant portion of backscatter occurs at the air/snow interface). We demonstrate that EUMETSAT Advanced Scatterometer (ASCAT) C-band scatterometer isotropic roughness data are sensitive to sea-ice roughness. Validation is provided by helicopter-mounted C-band nadir backscatter radar data and lidar swath data acquired in early spring, 2007, during the Australian-led Sea Ice Physics and Ecosystems eXperiment (SIPEX) campaign, and newly-acquired measurements of rugosity and snow/ice interface roughness from Autonomous Underwater Vehicle (AUV)-derived multibeam sonar acquired during the follow-up marine science voyage, SIPEX II. Using high-resolution sea-ice motion vectors from passive microwave imagery, we also investigate the links between large-scale sea-ice convergence and sub-metre-scale roughness.